1999
DOI: 10.1093/jn/129.7.1377
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nucleotides Augment Dextran Sulfate Sodium-Induced Distal Colitis in Rats

Abstract: We have previously shown that enteral and parenteral supplementation of nucleotides (NT) accelerates healing of small-bowel ulcers in rats with indomethacin-induced ileitis. The purpose of this study was to evaluate whether dietary NT supplementation would similarly affect ulcer healing in dextran sulfate sodium (DSS)-induced colitis in rats. Male Sprague-Dawley rats were randomly assigned to receive either nucleotide-free (NF) or NT-supplemented diets. After 2 d of prefeeding, colitis was induced by including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Similarly, a study in rats on the effect of dietary supplementation with a nucleoside/NT mixture showed that it exacerbated the injury associated with dextran sodium sulphate induced colitis. 16 Further studies on the potential benefits (and risks) of NT supplementation, therefore, appear justified. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in rats on the effect of dietary supplementation with a nucleoside/NT mixture showed that it exacerbated the injury associated with dextran sodium sulphate induced colitis. 16 Further studies on the potential benefits (and risks) of NT supplementation, therefore, appear justified. …”
Section: Discussionmentioning
confidence: 99%
“…Inflammation was assessed on the basis of criteria described in Table 1 (36,37). The final number was the sum of the diarrhea score, the visible fecal blood score, and the examination of the anus.…”
Section: Methodsmentioning
confidence: 99%
“…Indomethacinā€induced enteritis, a condition that shares clinical, histological, and pathophysiological characteristics with Crohn's disease, exhibited significant acceleration in ulcer healing and significant decreases in total ulcer length and number in the small intestine after exogenous nucleotide supplementation 62 , 63 . However, one of these same labs found that when dextran sulfate sodium salt (DSS) was used to induce distal colitis in rats, the nucleotideā€supplemented group showed more inflammation than the nucleotideā€free group, which achieved faster healing of the colitis 64 . In another model of colonic damage that used trinitrobenzene sulfonic acid (TNBS) to induce colitis, the control group also had improved recovery as compared with the nucleosideā€nucleotideā€supplemented group.…”
Section: Representative Animal Studies With Nucleotidesmentioning
confidence: 99%